Measuring and Comparing High School Teachers' and Undergraduate Students' Knowledge of Complex Systems - Lin Xiang; Zitsi Mirakhur; Andrew Pilny; Rebecca Krall (MDPI AG, 2024)
Complex systems (CSs) have garnered increasing attention in science education due to their prevalence in the natural world and their importance in addressing pressing issues such as climate change, pandemics, and biodiversity loss. However, the instruments for assessing one's CS knowledge are limited, and the knowledge of CSs among in-service teachers remains underreported. Guided by the complexity framework, we launched a study to develop and validate a survey instrument for measuring the knowledge of CSs among high school teachers and undergraduate students, as well as delineating the contours of their knowledge. In this article, we present the development and validation of a Complex Systems Knowledge Survey (CSKS), and we use the survey to compare the CS knowledge among 252 high school teachers and 418 undergraduate students in the United States. Our key findings include that (1) both high school teachers and undergraduates exhibit relatively low knowledge of decentralization and stochasticity, (2) undergraduates, especially those in non-STEM majors, demonstrate moderate to low knowledge of emergence, (3) few teachers and undergraduates differentiate between complicated and complex systems, and (4) teachers and undergraduates recognize CS examples across natural and social systems. The implications of our findings are discussed.